(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In this article Hanna Barvinok`s literary prose is considered in terms of Ukrainian mentality, that has an influence on character of literary сreative work and main archetypes of Ukrainian literature of the second half of 19th century.